Understanding intracardiac EGMs : a patient centered guide - Kusumoto, Fred (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley-Blackwell, 2015)
"This new book, designed as a series of cases, guides readers through the most common disorders, diagnostic and treatment modalities of electrophysiology"--Provided by publisher.
Chapter 21 Wide complex tachycardia case 2Chapter 22 Wide complex tachycardia case 3: premature ventricular contractions; Chapter 23 Wide complex tachycardia case 4; Chapter 24 Wide complex tachycardia case 5; Chapter 25 Wide complex tachycardia case 6; Chapter 26 Syncope; Bradycardia; Tachycardia; Chapter 27 Multiple choice questions and answers; Appendix; Index; EULA.
Includes index.
Machine generated contents note: Preface Chapter 1: EP Basics Chapter 2: SVT #1 Chapter 3: SVT #2 Chapter 4: SVT #3 Chapter 5: SVT #1 Chapter 6: SVT #4 Chapter 7: SVT #5 Chapter 8: SVT #6 Chapter 9: SVT #7 Chapter 10: SVT #8 Chapter 11: SVT #9 Chapter 12: SVT #10 Chapter 13: SVT #11 Chapter 14: Atrial Fibrillation Chapter 15: Atrial Tachycardia after Atrial Fibrillation Ablation #1 Chapter 16: Atrial Tachycardia after Atrial Fibrillation Ablation #2 Chapter 17: Atrial Tachycardia after Atrial Fibrillation Ablation #3 Chapter 18: Atrial Tachycardia after Atrial Fibrillation Ablation #4 Chapter 19: Atrial Tachycardia after Atrial Fibrillation Ablation #5 Chapter 20: WCT #1 Chapter 21: WCT #2 Chapter 22: PVCs Chapter 23: WCT #3 Chapter 24: WCT #4 Chapter 25:WCT #5 Chapter 26: Syncope Chapter 27: Problems Appendix Index.
Print version record and CIP data provided by publisher.
Keywords: Electrocardiography; Heart -- Electric properties; Medical; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Electrocardiography; Heart -- Electric properties; Electrophysiologic Techniques, Cardiac -- methods; Electrocardiography -- methods; Electronic books; Problems and Exercises